Sustainability of Pondok Institution in Kelantan: A Concept Study - Salmiah Ismail,; Zainab Ismail,; Salasiah Hanin Hamjah, (Penerbit Universiti Kebangsaan Malaysia, 2014)
Attitude thrilled with the current education system, which may give more guarantee to get job causing traditional education system is not seen as a serious concern for improvement both in terms of infrastructure or capital assistance. Traditional education system has actually contributed to the improvement of the current education system, which is undergoing a serious moral crisis. Traditional education system is also based on the basic knowledge of holiness, which such circumstances form a unique relationship student and teacher- intimate, respectful and spiritual. It is a unique pattern that elusive and rarely seen in the context of modern educational orientation. Based on the observation, the current situation shows that the traditional education system or mostly known as the pondok are still significant in the Malay community regardless of their background. Therefore this paper tries to highlight the significance of the traditional education system in the context of current society for bringing back this education system to people, which is full richness with Islamic spirit.